XV IAA General Assembly: Reviving academism - Kaftanov, Andrey (project baikal, 2025)
The article highlights the results of the XV General Assembly of the International Academy of Architecture held on September 9 in Rome. It presents the main theses of the IAA President Amedeo Schiattarella’s report, in particular, on the importance of raising awareness among international organizations about the importance of architectural culture as an integral expression of human values. It is noted that the participation of the Moscow Branch of the IAA in the Rome Biennale in 2026 will require the formation of a worthy exhibition, which, after a seven-year break, will be able to internationally demonstrate the achievements of modern architecture of Russia and the CIS countries